FISIOLOGY ADAPTATION OF SANDY ANEMONE (Heteractis malu) EXPOSED TO ELEVATED TEMPERATURES: LABORATORY CONDITION - Neviaty Putri Zamani (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Sandy anemone (Heteractis malu), belongs to Phylum Cnidaria, physiologically is very close to coral stone, which was a major component of coral reef ecosystems. As coral stone, Heteractis malu also has symbiotic algae (Zooxanthella). Physiologically, the alga symbiotic relationship of coral stone is almost similar with Heteractis malu. Maintaining Heteractis malu in the laboratory is relativly easier compared to that of coral stone. Advantages of the Heteractis malu vs. stone coral, its body is not covered by limestone makingit easier in processing analyses. The response of the anemone to stress is expected similar with coral stone. This research aims to analyze the response and adaptation of Heteractis malu to the temperature increase of 1 °C and 2 °C of the normal temperature (28 °C). The impact of temperature increases on Heteractis malu did not significantly affect the density of zooxanthellae, however, there was a significant increase of mitotic index. In addition, during a recovery process, Heteractis malu immune system did not show a significant increase based on its mitotic index results tended to decrease during the second phase of stress treatment.Keywords: Adaptation, sandy anemone (Heteractis malu), temperature increase,, zooxanthellae